Метрологическое обеспечение в Украине испытаний объектов энергетики, авиационной и ракетно-космической техники на стойкость к воздействию импульсов тока (напряжения) искусственной молнии и коммутационных импульсов напряжения - Баранов, М.И.; Буряковский, С.Г.; Рудаков, С.В. (Електротехніка і електромеханіка, 2018)
Изложено современное состояние метрологического обеспечения в Украине натурных испытаний объектов промышленной энергетики, авиационной и ракетно-космической техники на стойкость к прямому воздействию на них мощных импульсов тока (напряжения) искусственной молнии и апериодических коммутационных импульсов напряжения. Показано, что подобные испытания технических объектов на молниестойкость и коммутационную стойкость
могут проводиться в соответствии с требованиями нормативных документов США SAE ARP 5412: 2013, SAE ARP
5416: 2013, международного стандарта IEC 62305-1: 2010 и стандарта ГОСТ 1516.2-97 в полевых условиях на уникальных отечественных высоковольтных сильноточных электроустановках, оснащенных современными измерительными средствами. Описаны основные технические характеристики разработанных и созданных в НИПКИ
«Молния» НТУ «ХПИ» для метрологического обеспечения натурных испытаний указанных технических объектов на
молниестойкость и коммутационную стойкость: измерительных коаксиальных сильноточных шунтов типа ШК300М1 и ШК-300М2, емкостных и омических высоковольтных и сверхвысоковольтных делителей напряжения типа
ЕДН-100, ЕДН-1,2, ОДН-1,2 и ОДН-2,5. Приведены примеры практического использования при натурных испытаниях
на молниестойкость и коммутационную стойкость отмеченных технических объектов указанных нестандартизованных измерительных средств собственного изготовления. Викладено сучасне положення метрологічного забезпечення в Україні натурних випробувань об'єктів промислової енергетики, авіаційної і ракетно-космічної техніки на стійкість до прямої дії на них потужних імпульсів струму (напруги) штучної блискавки та аперіодичних комутаційних імпульсів напруги. Показано, що подібні випробування технічних об’єктів на блискавкостійкість та комутаційну стійкість можуть проводитися відповідно до вимог нормативних документів США SAE ARP 5412: 2013, SAE ARP 5416: 2013, міжнародного стандарту IEC 62305-1: 2010 і стандарту ГОСТ 1516.2-97 в польових умовах на унікальних вітчизняних високовольтних сильнострумних електроустановках, які оснащені сучасними вимірювальними засобами. Описані основні технічні характеристики розроблених і створених в НДПКІ «Молнія» НТУ «ХПІ» для метрологічного забезпечення натурних випробувань вказаних технічних
об'єктів на блискавкостійкість та комутаційну стійкість: вимірювальних коаксіальних сильнострумних шунтів типу ШК-300М1 і ШК-300М2, ємнісних і омічних високовольтних та надвисоковольтних подільників напруги типу
ЄПН-100, ЄПН-1,2, ОПН-1,2 і ОПН-2,5. Приведені приклади практичного використання при натурних випробуваннях
на блискавкостійкість та комутаційну стійкість відмічених технічних об'єктів вказаних нестандартізованних вимірювальних засобів власного виготовлення Purpose. Presentation and analysis of the modern state of the
metrology support in Ukraine of model tests of equipment of objects of energy on resistibility to the action of pulsed current (voltage) of artificial lightning and commutation pulses of voltage, and
also objects of aviation and space-rocket engineering on resistibility to lightning. Methodology. Electrophysics bases of engineering of high-voltage and large pulsed currents, theoretical
bases of the electrical engineering, technique of the strong electric
and magnetic fields, and also measuring technique. Scientific
methods of analysis of scientific and technical information. Results. Information is resulted, touching the modern consisting of
Ukraine of providing high-voltage measuring facilities conducted
on requirements of the normative documents of the USA of SAE
ARP 5412:2013, SAE ARP 5416:2013, International Standard of
IEC 62305-1:2010 and Standard GOST 1516.2-97 model tests of
equipment of objects of energy on resistibility to lightning and
commutation resistibility, and also objects of aviation and spacerocket engineering on resistibility to lightning. It is marked that
similar measuring facilities are not made by domestic industry. It
is indicated that R&DPCI “Molniya” of the NTU “KhPI” disposes the proper measuring facilities of the own making, passing
a state metrology check (calibration). Basic technical descriptions
are described developed and created at this Institute: high-voltage
high-current shunts of type of SC-300M1 and SC-300M2, intended for measuring of micro- and millisecond pulses of current
amplitude to ±220 кА with the integral of their action to 15·106
J/Ohm; capacitive (type of CDV-100 and CDV-1,2) and ohmic
(type of ODV-1,2 and ODV-2,5) dividers of pulsed voltage of
micro- and millisecond duration, capable not only to measure but
also form on the tested electric loading standard (non-standard)
storm and commutation pulses of voltage amplitude to ±2 MV.
Originality. First in the generalized kind possibilities are developed and created by the domestic scientific and technical workers
of high-voltage high-current measuring facilities, intended for the
aims of the metrology providing of model tests in obedience to the
requirements of domestic and foreign normative documents of
equipment of objects of energy on resistibility to lightning and
commutation resistibility, and also objects of aviation and spacerocket engineering on resistibility to lightning. Practical value.
Application in practice of model tests on powerful high-voltage
pulsed current (voltage) of artificial lightning and commutation
pulses of voltage of electrical equipment and component elements
of objects of energy, aviation and space-rocket engineering on
resistibility to lightning and commutation resistibility of the described special high-voltage measuring facilities will be instrumental in the decision of global in the world problem of protection
from lightning of ground and air-based technical objects and to
the increase of their strength security